Performance analysis of Super 15 rugby match-play using portable micro-technology - McLellan, C. P.; Coad, S.; Marsh, D.; Lieschke, M. (Journal of Athletic Enhancement, 2013)
Advances in sports performance analysis technologies such as portable global positioning system (GPS) and integrated accelerometry have enabled investigators to accurately quantify the demands of competitive match-play in contact sports such as Rugby Union - The aim of the present study was i) to examine the physiological demands of competitive Super 15 Rugby match-play using portable Global Positioning Systems (GPS) and integrated accelerometry to monitor the demands of match-play and ii) examine positional comparisons to determine if a player`s physiological requirements are influenced by their playing position during Super 15 Rugby competition. Five elite male Rugby Union players were monitored during eleven regular season competition matches using portable GPS and integrated accelerometry. There was a significant (p>0.05) difference in the total and relative distance travelled and between backs and forwards during match-play. Backs achieved greater maximum running speed, completed a greater number of sprints, had greater time between sprints, and covered more distance sprinting than forwards. Forwards experienced significantly (p>0.05) more total impacts than backs during match-play while the number of impacts recorded in zone 4 (7.1-8.0 G), zone 5 (8.1-10.0 G) and zone 6 (= 10.1 G) were significantly (p>0.05) greater for forwards than backs. The present study provides insight into the variation in positional demands between forwards and backs and the intense physical nature of Super 15 Rugby Union match-play. These data may assist coaching and performance staff to develop and implement individualised and position specific training regimes to optimise on-field performance.